IMPLEMENTASI PELAYANAN AKHIR PEKAN DI KECAMATAN BANYUMANIK KOTA SEMARANG JAWA TENGAH - Tasya Monica, Bella; Maesaroh, Maesaroh; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
This study aims to analyze the implementation of the weekend service program in Banyumanik District, Semarang City. Weekend service is a program carried out by the Semarang City Government to improve public services, especially in terms of administration and licensing. This is done as an effort to improve public services and fulfill the rights of the community to obtain quality public services. The type of research used is a qualitative descriptive method. Data collection techniques used are observation, interviews and documentation. The data analysis technique used is descriptive The results of the study indicate that the implementation of the weekend service program in Banyumanik District has been carried out systematically in accordance with established procedures. However, there are still several obstacles faced, namely in the disposition, namely the absence of incentives given to Banyumanik District employees for the weekend service program. The conclusion of this study is that the implementation of policies in Banyumanik District aims to achieve the target of more accessible public services, especially for workers who cannot take care of administration on weekdays. The weekend service program is designed to change the image of complicated public services, combine administrative services with entertainment, and support local MSMEs. Despite challenges such as high number of visitors in the morning and decreasing number of administrative service users, the program is still appreciated by the community. This is because the program facilitates access to services and supports the local economy. Overall, the program has succeeded in improving the quality of public services to be more efficient and responsive.